PENERAPAN METODE STUDENT CENTERED LEARNING UNTUK KEAKTIFAN SISWA KELAS 8.9 SMP NEGERI 26 PALEMBANG - Selvi Oktarina; Nini Rafika; Fajri Yumeihaimi; Muhammad Syahbani; Syarnubi Syarnubi; Sukirman, Sukirman (PAI RAFAH, 2024)
Basically This research aims to analyze the influence of the student centered learning method on the learning motivation of grade 8 students. The student centered learning method is an approach that emphasizes individual attention to the needs and development of each student, including emotional, social and academic support. This study uses a descriptive qualitative research design with data collection through observation, interviews and motivational documentation studies. The research subjects consisted of 37 grade 8 students at SMP Negeri 26 Palembang who were divided into discussion groups. The discussion group is given material to conduct group discussions in the form of a student centered learning method. From the results of research and observations carried out, it shows that there is a significant increase in learning motivation in discussion groups. This increase includes aspects of interest in learning, effort and perseverance. These findings indicate that the student centered learning method is effective in increasing the learning motivation of grade 8 junior high school students, so it is recommended that it be implemented more widely in various educational contexts.